Action mechanism of early cerebral injuries after spontaneous subarachnoid hemorrhage by silence Ghrelin and angiogenic factor with G-patch and FHA domain 1. Issue 3 (1st March 2022) - Tang, Jianxun; Hu, Ligang; Long, Feng; Zhang, Jie; Tang, Jingfeng
ABSTRACT: The objective of the research was to investigate action mechanism of oxidative stress and cerebral injuries after subarachnoid hemorrhage (SAH) by Ghrelin and angiogenic factor G-patch and FHA domain 1 (Aggf1) and offer new research ideas to SAH clinical treatment and SAH-induced early cerebral injuries. SAH rat models were prepared by prechiasmatic anterior cistern injection. Specific Ghrelin and Aggf1 small interfering ribonucleic acid (siRNA) were designed and injected into silence Ghrelin or Aggf1 in rat left lateral ventricles. Rats were divided randomly into sham-operated (sham), SAH model, negative control siRNA, Ghrelin silence (Ghrelin (-/-) ), and Aggf1 silence groups. Changes of rat neurological impairment, encephaledema, cerebral tissue phosphorylated protein kinase (p-Akt), and content changes of caspase-3 protein and oxidative stress indexes were observed, including glutathione (GSH) and oxidized glutathione (GSSG). Results showed scores of neurological impairment and water content in SAH model group were reduced compared with sham group, while p-Akt protein and GSH contents were enhanced. However, caspase-3 protein and GSSG contents were declined, showing statistically meaningful difference ( P < 0.05). Compared with SAH model group, scores of neurological impairment, cerebral tissue water content, and caspase-3 protein and GSSG contents in silence Ghrelin and Aggf1 groups were increased, while p-Akt protein and GSH contents were decreased, demonstrating statistically meaningful difference ( P < 0.05). To conclude, silence Ghrelin and Aggf1 aggravated early cerebral injuries after SAH, revealing that Ghrelin and Aggf1 could protect brains to some degree. GRAPHICAL ABSTRACT: uf0001